Applying a Hybrid Modeling Approach to Evaluate Potential Pesticide Effects and Mitigation Effectiveness for an Endangered Fish in Simulated Oxbow Habitats. (5th August 2021) - Schmolke, Amelie; Bartell, Steven M.; Roy, Colleen; Desmarteau, Dean; Moore, Angela; Cox, Megan J.; Maples‐Reynolds, Nikki L.; Galic, Nika; Brain, Richard
Abstract: The occurrence of some species listed under the United States' Endangered Species Act in agricultural landscapes suggests that their habitats could potentially be exposed to pesticides. However, the potential effects from such exposures on populations are difficult to estimate. Mechanistic models can provide an avenue to estimating the potential impacts on populations, considering realistic assumptions about the ecology of the species, the ecosystem it is part of, and the potential exposures within the habitat. In the present study, we applied a hybrid model of the Topeka shiner ( Notropis topeka ), a small endangered cyprinid fish endemic to the US Midwest, to assess the potential population‐level effects of realistic exposures to a fungicide (benzovindiflupyr). The Topeka shiner populations were simulated in the context of the food web found in oxbow habitats that are the focus of ongoing habitat restoration efforts for the species. We applied realistic, time‐variable exposure scenarios and represented lethal and sublethal effects to individual Topeka shiners using toxicokinetic–toxicodynamic models. With fish in general showing the highest sensitivity to the compound, direct effects on simulated Topeka shiner populations governed the population‐level effects. We characterized the population‐level effects of different exposure scenarios with exposure multiplication factors (EMFs) applied. The introduction of a vegetative filter strip (VFS; 15 ft; 4.6 m) between the treated area and the oxbow habitat was shown to be effective as mitigation because EMFs were 2 to 3 times higher than for the exposure scenario without VFS. Environ Toxicol Chem 2021;40:2615–2628. © 2021 SETAC